(3GdCSGdjH GdcejI GdEdcJQhfjI (B/s - (3GdUjQaj, eMeOs ([(3Ohf ecGf(B]: s (3OGQ GdcJGH GdbGfhfj(B, s)
-(3GdNWQ , GdJCejf , GdJCejf Ydi GdMjGI , GdJCejf GdHMQj, GdJCejf GdELJeGYj , GdJCejf VO GdMQjb , JCejfGJ GdeSDhdjI GdeOfjI JCejfGJ GdSjGQGJ , JCejfGJ GdWjQGfs
(3GdeQGLY U(B.677s